212k views
5 votes
What is -4 (-6x + 3) = 12

User Snowfox
by
5.2k points

2 Answers

0 votes

Answer:

Step-by-step explanation: heyy... the pic attached below shows all the steps with a brief explanation. I hope it helps u !!!

What is -4 (-6x + 3) = 12-example-1
User Zondo
by
6.0k points
2 votes

Answer: x = 1

Explanation:

Simplifying

-4(-6x + 3) = 12

Reorder the terms:

-4(3 + -6x) = 12

(3 * -4 + -6x * -4) = 12

(-12 + 24x) = 12

Solving

-12 + 24x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.

-12 + 12 + 24x = 12 + 12

Combine like terms: -12 + 12 = 0

0 + 24x = 12 + 12

24x = 12 + 12

Combine like terms: 12 + 12 = 24

24x = 24

Divide each side by '24'.

x = 1

Simplifying

x = 1

User Paul Walczewski
by
5.8k points